Differences in HDL Remodeling during Healthy Pregnancy and Pregnancy with Cardiometabolic Complications - Marko Stankovic; Aleksandra Zeljkovic; Jelena Vekic; Tamara Antonic; Daniela Ardalic; Milica Miljkovic-Trailovic; Jelena Munjas; Marija Saric Matutinovic; Tamara Gojkovic; Snezana Jovicic; Zeljko Mikovic; Aleksandra Stefanovic (MDPI AG, 2024)
This study investigated the longitudinal trajectory of changes in antioxidative and anti-inflammatory high-density lipoprotein (HDL) components during healthy pregnancy and pregnancy with cardiometabolic complications. We recruited and longitudinally followed 84 women with healthy pregnancies and 46 pregnant women who developed cardiometabolic pregnancy complications (gestational diabetes mellitus and hypertensive disorders of pregnancy). Their general lipid profiles, oxidative stress status, inflammatory status, and antioxidative and anti-inflammatory HDL components were analyzed. The results of our study confirmed the expected trajectory for the routine lipid parameters. Our study results indicate more intensive oxidative stress and a higher level of inflammation in the group with complications compared with the control group. Sphingosine-1-phosphate (S1P) was significantly lower in the first trimester in the group with complications compared with the control group (p < 0.05). We did not find significant differences in the apolipoprotein A1 (Apo A1) concentrations in the first trimester between the control group and the group with complications, but in the second and third trimesters, the group with complications had significantly higher concentrations (p < 0.001, p < 0.05, respectively). The S1P, paraoxonase 1 (PON1), and serum amyloid A (SAA) concentrations were significantly lower in the group with complications in the first trimester. During the second trimester, only the SAA concentrations were identified as significantly lower in the group with complications compared with the control group, while in the third trimester, the PON1, apolipoprotein M (Apo M), and SAA concentrations were all significantly lower in the group with complications. Through a multivariate binary logistic regression analysis, the S1P concentration in the first trimester was distinguished as an HDL-associated marker independently associated with cardiometabolic pregnancy complications. In conclusion, our study results showed that HDL remodeling differs between healthy pregnancies and pregnancies with maternal cardiometabolic complications, with changed HDL composition and functionality consequently impacting its biological functionality in the latter case.